EFEK ANTIANGIOGENIK EKSTRAK METANOL AKAR PASAK BUMI (Eurycoma longifolia, Jack) PADA MEMBRAN KORIO ALANTOIS (CAM) EMBRIO AYAM YANG TERINDUKSI bFGF - Nina Salamah; Sugiyanto Sugiyanto; Mae Sri Hartati; Farida Hayati (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Angiogenesis is a neovascularization process which its function is to supply nutrient and oxygen for cell survival. Pasak bumi is one of the Indonesian original plants having anti cancer activity. Extract of methanol, buthanol, kloroform, and water akar pasak bumi was proved to have cytotoxic effect on cancer cell culture. This research aim to know activity of antiangiogenic extract of metanol akar pasak bumi at chorioallantoic membrane of chicken embryo. Antiangiogenic activity test conducted by divide 8-9 days old egg embrio into 8 groups. Group I as paper disc control, group II as bFGF control, group III as bFGF control + DMSO 0.8% solvent, group IV, V, VI, VII, and VIII as groups of treatment. Each groups of treatment were gave by bFGF 1ng/µL extract of metanol akar pasak bumi respectively with concentration 20, 40, 60, 80 and 100 µg/mL concentration. After 3 days incubation, then the chorioallantoic membrane macroscopic and microcospically analized. The antiangiogenic activity extract of metanol akar pasak bumi at chorioallantoic membrane bFGF induce at used concentration, that is start from 40 µg/mL concentration. The increases of the concentration also increase the prohibition activity to angiogenesis.